(untitled) (Fiep Bulletin - online, 2014)
Currently in Brazil, according to the IBGE (2006), the elderly account for about 9% of the population, totaling 17 million people over 60 years, and the prospects of the UN in the next 20 years, is that this percentage increases to 16 %, which is beyond the Brazilian live longer, have more elderly in the population. In old age, the difficulty of tasks is evident, the distances are "longer", the stairs are harder to climb, the streets are more dangerous to cross, "the world becomes a threat to the elderly." Exercise is one of the most effective speeches about the improvement of the quality of life of the elderly, therefore helps in the control of the changes by the process of aging, promoting autonomy and independence in activities of daily life. Objective: To evaluate the effects of the practice of physical activity (against resistance training) on the health of the elderly. Methodology: Through descriptive method using a methodology of investigation. The sample was composed of 40 elderly of both genders, with 20 men and 20 women in the age group between 60 to 80 years practitioners of exercises against resistance (bodybuilding), and at least 12 months in academies located in the South of the Borough the Rio de Janeiro. Individuals volunteers responded four questionnaires being them: IPAQ short version (questionnaire international physical activity); NAHAS assessment of the profile of the lifestyle, WHOOLD quality of life for older people and a questionnaire PILOT. Results: To correlate the questionnaires, it was found that physical activity in question both in IPAQ, NAHAS, WHOOLD and PILOT got to be a satisfactory degree on the level of physical activity undertaken by senior studied, and the question was no relationship or social participation also a satisfactory average significantly between NAHAS and WHOOLD. Conclusion: At the end of the study, one can observe that the constant practice of the year against resistance presented a very significant result especially in motor respectively, and in other aspects studied for the improvement of the quality of life of older people. These results should be taken into consideration by the professionals who work or will work with the prescription of exercises in individuals of the third age, as it demonstrates the existence of a capacity to perform activities